Social Cognition Deficits as a Target of Early Intervention for Psychoses: A Systematic Review - Yamada, Yuji; Inagawa, Takuma; Sueyoshi, Kazuki; Sugawara, Norio; Ueda, Natsuki; Omachi, Yoshie; Hirabayashi, Naotsugu; Matsumoto, Madoka; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2019)
Backgrounds: Social cognition deficits are a core feature of schizophrenia, and deteriorate functionality of patients. However, evidence is sparse for the treatment effect on social cognition impairments in the early stage of psychosis. Here, we provide a systematic review of the literature on social cognitive impairment in early psychosis in relation to its intervention. Methods: A literature search was conducted on English articles identified by Web of Science and PubMed databases, according to the guidelines of the PRISMA statement. Results: Five papers met the inclusion criteria. Results from two studies of cognitive training, and one study of modafinil indicate positive results regarding outcomes related to social cognition outcomes in patients with early psychosis. On the other hand, two studies with oxytocin and modafinil did not suggest such effects. Conclusions: Further research is warranted to explore the benefit of early intervention into disturbances of social cognition in psychoses.